(untitled) (Indian Journal of Public Health Research & Development, 2026)
Context: Urinary schistosomiasis, caused by Schistosoma haematobium, was once a major neglected tropical disease (NTD) endemic across sub-Saharan Africa, the Nile Valley, and parts of the Middle East, including Iraq. The disease relies on freshwater snails of the genus Bulinus as an obligate intermediate host. This review aimed to characterise the full epidemiological trajectory of S. haematobium in Iraq from earliest records to the present day. Methods: Epidemiological databases (Communicable Diseases Control Center/Iraq, PubMed, ISI, Scopus) were searched for records spanning 1919 to July 2025. Results: Iraq’s National Schistosomiasis Control Programme achieved a dramatic decline in infection prevalence — from 27% in 1954 to 0.02% in 2002 — through integrated strategies encompassing mass treatment with praziquantel, molluscicide-based snail control, engineering interventions, and sustained health education. No locally acquired cases have been recorded since 2011, and comprehensive vector surveillance has confirmed the absence of Bulinus truncatus from all 19 governorates. Iraq is currently in the WHO-guided elimination certification process. Conclusions: Urinary schistosomiasis has been effectively eliminated as a public health problem in Iraq through decades of coordinated national and international effort. Pending WHO/EMRO formal verification, Iraq stands as a regional model for NTD elimination in the Middle East.